Metagenomic insights into the rumen epithelial integrity responses to the vitamin B1 supplement under high-concentrate diets treatments - Ma, Peng; Sun, Chaoqun; Liu, Minze; You, Hongnan; Shen, Yao; Kang, Yajie; Sun, Yuqin; Yang, Zhengang; Ma, Pengyun; Yang, Liang; Xue, Fuguang (Frontiers in Microbiology, 2022)
Subacute ruminal acidosis (SARA) becomes the most common nutritional metabolic disease in high-yielding dairy cows and later fatting beef cattle because of the increasing consumption of high-concentrate diets in modern feeding patterns. Our previous research found a certain piece of evidence that adding 180 mg thiamine/kg DMI could increase the rumen pH and regulate the structure of the rumen microbial community in vivo. However, there is still limited experimental data on the effects of SARA on thiamine status, the damage to the structure of rumen epithelial cells, and the underlying mechanism of the epithelium alterations. For this purpose, a total of 18 Angus bulls (average 22.0-months-old) with an average live weight of 567.6 ± 27.4 kg were randomly allocated into a control treatment (CON), a high-concentrate diet treatment (HC), and a high-concentrate diet with the vitamin B1 supplement treatment (HCB). All bulls were conducted with a 7-day adjustment period followed by a 60-day-long main feeding procedure. Results indicated that ADFI and ADG significantly decreased in the HC treatment compared with CON (P < 0.05), while significantly increased after the VB1 supplement (P < 0.05). Besides, ruminal acetate content was significantly downregulated while propionate was significantly upregulated under the HC treatment compared with CON (P < 0.05); however, these alterations showed a completely inverse regulatory effect on the VB1 supplement compared with HC (P < 0.05). These changes causatively induced a significant decrease in the A/P ratio in the HC treatment compared with CON and HCB treatments (P < 0.05). Bacterial communities in the HC treatment could be separated from those in CON through PCoA axes 1 and 2. Meanwhile, the VB1 supplement significantly altered the bacterial communities compared with the HC treatment, except for HCB-3. Furthermore, the HC treatment significantly upregulated the expression of JNK, Bax, Caspase-8, Caspase-3, Caspase-9, and Cyt-C compared with CON, while significantly downregulated the expression of Bcl-2. The VB1 supplement showed a complete converse gene expression compared with HC. In conclusion, the VB1 supplement could effectively attenuate the alterations that occurred when exposed to high-concentrate diets, and help promote production performance through increased fermentability.